Challenges in designing interventions for food insecure families with food allergy in a Californian latinx cohort - Marleni Albarran; Emily Brown; Erin Martinez; Andrew R. Chin; Sayantani B. Sindher; Christopher M. Warren; R. Sharon Chinthrajah (Frontiers in Allergy)
Food allergy poses substantial social, economic, and quality of life burdens which are even heavier for families that are struggling with food insecurity. In the United States (US), food insecurity disproportionately affects vulnerable and historically marginalized communities, such as Latino/a/x and Black households. Targeting these disparities via our recent Food Equality Initiative (FEI) research intervention was challenging due to the barriers faced by the target underserved populations, which included poor digital literacy, language barriers, and limited access to necessary resources. These barriers hindered our efforts to promote access to nutritious and safe food options for food-insecure families, potentially further exacerbating health disparities. Here we discuss common challenges and opportunities associated with conducting research interventions in underserved communities in the US—leveraging our experiences designing and implementing an intervention to improve food allergy management through supplemental nutrition assistance in a predominantly Spanish-speaking, lower-income neighborhood in Northern California. We also provide recommendations for other researchers regarding how to tailor research strategies to address these challenges, and in so doing reduce health disparities and promote positive health outcomes for vulnerable and historically marginalized communities.